A New Vision about Folliculitis Decalvans and Lichen Planopilaris: Two Distinct Entities or a Continuous Phenotypic Spectrum? - Marcos-Pinto, Ana (2021)
Folliculitis decalvans and lichen planopilaris have been considered two distinct cicatricial alopecias. However, biphasic presentation of folliculitis decalvans - lichen planopilaris in the same patient has been recently described, therefore raising the doubt if they are two distinct entities or a continuous phenotypic spectrum.We describe the case of a man who presented clinical, trichoscopic, and histopathological features of both entities. Moreover, we discuss current theories about the pathogenesis of the two diseases and their coexistence in the same patient. The recognition of similar cases allows to optimize the approach and treatment.